Exploiting biological diversity and genomic aberrations in chronic lymphocytic leukemia - Seiffert, Martina; Dietrich, Sascha; Jethwa, Alexander; Glimm, Hanno; Lichter, Peter; Zenz, Thorsten (Leukemia and lymphoma, 2012)
There is remarkable heterogeneity in the clinical course and biological characteristics of patient subgroups with chronic lymphocytic leukemia (CLL). Mutations of key tumor suppressors (ATM, miR-15a/16-1 and TP53) have been identified in CLL, and these aberrations are important “drivers” of the disease and some of its clinical characteristics. While some mutations are associated with poor outcome [particularly del(17p) and TP53 mutation], others are linked to a favorable clinical course [e.g. del(13q) as sole aberration]. In addition to genetic aberrations, antigen drive and microenvironmental interactions contribute to the pathogenesis of CLL. How the genetic aberrations impact on the process of antigen drive or microenvironmental interactions is currently unclear. Our improved understanding of the biology and clinical course of specific genetic subgroups is beginning to be translated into more specific and targeted treatment approaches. As a result, genetic subgroups are treated in distinct protocols. This review summarizes the contribution of the microenvironment and the most important genetic aberrations in CLL and how our improved knowledge of the biology of CLL may translate into improved treatment results.
Published online: 06 Dec 2011
Gesehen am 29.06.2018